ANALISIS PEMASARAN DAN DESAIN SISTEM PERBAIKAN KUALITAS TEPUNG TALAS BENENG - Zulfatun Najah; Winda Nurtiana (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
Problems faced in the beneng taro flour production system is quality and quantity. Therefore, it is necessary to analyze and design the improvement of the quality of beneng taro flour. The purpose of this paper is to analyze and design a quality improvement model in taro beneng. The system design stage begins with analyzed the entities of beneng taro flour production, analyzed the market, determined the quality performance indicators of the beneng taro flour, evaluated the quality, and improvements designed of the beneng taro flour. In the needs analysis, it produces input, output, stakeholder roles, control, and resources. The quality performance indicators is done by listing the quality attributes that determine quality performance. In this model, there are 8 quality dimensions and 16 of quality attributes. Quality evaluation is then carried out by comparing product performance and consumer expectations. Design improvement is done by analyzing the results of quality evaluation. Based on the analysis, there are 6 product attributes that need improvement including texture, color, suitability of product information, price suitability, ease of access and product popularity.